Aglycemic HepG2 Cells Switch From Aminotransferase Glutaminolytic Pathway of Pyruvate Utilization to Complete Krebs Cycle at Hypoxia - Ježek, Jan; Plecitá-Hlavatá, Lydie; Ježek, Petr (Frontiers in Endocrinology, 2018)
Human hepatocellular carcinoma HepG2 cells are forced to oxidative phosphorylation (OXPHOS), when cultured in aglycemic conditions at galactose and glutamine. These OXPHOS cells represent a prototype of cancer cell bioenergetics with mixed aerobic glycolysis and OXPHOS. We aimed to determine fractions of i) glutaminolytic pathway involving aminotransferase reaction supplying 2-oxoglutarate (2OG) to the Krebs cycle vs. ii) active segment of the Krebs cycle with aconitase and isocitrate dehydrogenase-3 (ACO-IDH3), which is typically inactive in cancer cells due to the citrate export from mitochondria. At normoxia, OXPHOS cell respiration was decreased down to 15% and 10% by the aminotransferase inhibitor aminooxyacetate (AOA) or with AOA plus the glutamate-dehydrogenase inhibitor bithionol, respectively. Phosphorylating to non-phosphorylating respiration ratios dropped from >6.5 to 1.9 with AOA and to zero with AOA plus bithionol. Thus normoxic OXPHOS HepG2 cells rely predominantly on glutaminolysis. Addition of membrane-permeant dimethyl-2-oxoglutarate (dm2OG) to inhibited cells instantly partially restored respiration, evidencing the lack of 2OG-dehydrogenase substrate upon aminotransferase inhibition. Surprisingly, after 72 hours of 5% O2 hypoxia, the AOA (bithionol) inhibition ceased and respiration was completely restored. Thus in aglycemic HepG2 cells, the hypoxia-induced factor (HIF) upregulation of glycolytic enzymes enabled acceleration of glycolysis pathway, preceded by galactolysis (Leloir pathway), redirecting pyruvate via still incompletely blocked pyruvate dehydrogenase toward the ACO-IDH3. Glycolytic flux upregulation at hypoxia was evidently matched by a higher activity of the Leloir pathway in OXPHOS cells. Hypoxic OXPHOS cells increased 2-fold the NADPH oxidase activity, whereas hypoxic glycolytic cells decreased it. OXPHOS cells and glycolytic cells at 5 mM glucose decreased their reduced glutathione fraction. In contrast to aglycemic cells, glycolytic HepG2 cells decreased their respiration at hypoxia despite the dm2OG presence, i.e. even at unlimited respiratory substrate availability for 72 hours at 5% O2, exhibiting the canonical HIF-mediated adaptation. Nevertheless, their ATP content was much higher with dm2OG as compared to its absence during hypoxic adaptation. Thus the metabolic plasticity of cancer cells is illustrated under conditions frequently established for solid tumors in vivo, such as aglycemia plus hypoxia. Consequently, a wide acceptance of the irreversible and exclusive Warburg phenotype in cancer cells is incorrect.